A laterally-fused N-heterocyclic carbene framework from polysubstituted aminoimidazo[5,1-b]oxazol-6-ium salts - Gillie, Andrew D.; Wakeling, Matthew G.; Greene, Bethan L.; Male, Louise; Davies, Paul W. (Beilstein Journal of Organic Chemistry, 2024)
A polysubstituted 3-aminoimidazo[5,1-b]oxazol-6-ium framework has been accessed from a new nitrenoid reagent by a two-step ynamide annulation and imidazolium ring-formation sequence. Metalation with Au(I), Cu(I) and Ir(I) at the C2 position provides an L-shaped NHC ligand scaffold that has been validated in gold-catalysed alkyne hydration and arylative cyclisation reactions.
Keywords: annulation; carbene; gold; imidazolium; NHC